The Sphinx That Traveled to Philadelphia The Story of the Colossal Sphinx of Ramses the Great in the Penn Museum - Wegner, Josef (University of Pennsylvania Press, 2015)
Written to celebrate the centennial of the Sphinx's arrival in Philadelphia, The Sphinx That Traveled to Philadelphia tells the fascinating story of the colossal sphinx that is a highlight of the Penn Museum's Egyptian galleries and an iconic object for the Museum as a whole. The narrative covers the original excavations and archaeological history of the Sphinx, how it came to Philadelphia, and the unexpected ways in which the Sphinx's story intersects with the history of Philadelphia, the University of Pennsylvania, and the Museum just before World War I.The book features ample illustrations-photographs, letters, newspaper stories, postcards, maps, and drawings-drawn largely from the extensive materials in the Museum Archives. Images of related artifacts in the Penn Museum's Egyptian collection and other objects from the Egyptian, Near East, and Mediterranean Sections (many not on view and some never before published), as well as pieces in museums in the United States, Europe, and Egypt, place the story of the Penn Museum Sphinx in a wider context. The writing style is informal and text is woven around the graphics that form the backbone of the narrative. The book is designed to be of interest to a wide audience of adult readers but accessible and engaging to younger readers as well